2009
DOI: 10.1002/jmv.21432
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability and phylogeny of the high‐risk HPV‐31, ‐33, ‐35, ‐52, and ‐58 in central Brazil

Abstract: More than 100 HPV types have been described, 13 of which are classified as high-risk due to their association with the development of cervical cancer. The intratype genomic diversity of HPV-16 and -18 has been studied extensively, while little data have been generated for other less common high-risk types. The present study explores the nucleotide variability and phylogeny of the high-risk HPV-31, -33, -35, -52, and -58, in samples from Central Brazil. For this purpose, the LCR and the E6 and L1 genes were seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
46
1
4

Year Published

2010
2010
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 34 publications
10
46
1
4
Order By: Relevance
“…HPV 52 in our study had variant lineages similar to those reported by previous studies. 18,19,21,23 In a Canadian study on E6-E7-LCR segment of 111 HPV 52 samples, the prototype-like group was the more common type. 18 However, the prototype-like group was observed in only two samples in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HPV 52 in our study had variant lineages similar to those reported by previous studies. 18,19,21,23 In a Canadian study on E6-E7-LCR segment of 111 HPV 52 samples, the prototype-like group was the more common type. 18 However, the prototype-like group was observed in only two samples in our study.…”
Section: Discussionmentioning
confidence: 99%
“…19 Phylogenetic analysis of HPV 52 was constructed using LCR sequences of four samples detected in central Brazil, along with those from other parts of the world submitted to the GenBank database. 21 Four clusters were identified and two of which could be classified as Asian and European branches. The HPV 52 B variant in our study could be regarded as an Asian cluster and the A variant (prototypelike) as a European cluster.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…1 Clinical relevance of HPV31 variants has been rarely described, [13][14][15] although the intratypic variations in the L1, E6, E7 and long control region were recognized. [14][15][16][17][18][19][20][21] A recent study by Chen et al 22 has defined HPV31 variants as A, B and C lineages based on the whole genome analyses. This provides a basis to view the variant as a distinct phylogenetic entity and better understand the variant-related pathogenesis of cervical lesion.…”
mentioning
confidence: 99%
“…HPV-52 is phylogenetically related to HPV-16 (7), whose variants could be divided into Asian-American, African and European lineages, whose carcinogenic risks have been extensively studied (8,9). Similarly, the variants of HPV-52 could be classified as Asian and European lineages (10), with a mean sequence difference of 1.8-2.0% (11). However, limited data of HPV-52 variants is available from the mainland of China (12).…”
Section: Introductionmentioning
confidence: 99%